Potencial de germinación de semillas en un bosque secundario premontano en San Pedro de Montes de Oca, Costa Rica - Di Stéfano G., José Fco. (Universidad de Costa Rica, 1992)
The seed bank of a small preserve (Premontane tropical forest) in Costa Rica, was analyzed. The area was divided into three zones, one of which was dominated by a vine (lpomoea sp.). Soil samples (10.1 cm. diam. x 12 cm deep) from each zone were planed in the greenhouse at two light intensities: total and al 50 %. Field pIots (1 m2) were also established at eaeh of the zones and analyzed a year later. Samples and plats were dominated by heroaceous speeies with few trees and a very low eorrelation with the actual vegetatíon. At 50 % light intensity, less than 11 % of lhe total individuals were present. The site with lpomoea sp. showed a strong reduction in the number of individuals: 30 to 84 % less when eompared with the other zones. The progressive elimination of lpomoea (by opening small clearings and planting native tree speeies) would promote vegetation development and inerease diversity.